2014
DOI: 10.1155/2014/790902
|View full text |Cite|
|
Sign up to set email alerts
|

Hyperglycemia Induces Toll-Like Receptor-2 and -4 Expression and Activity in Human Microvascular Retinal Endothelial Cells: Implications for Diabetic Retinopathy

Abstract: Diabetic retinopathy (DR) causes visual impairment in working age adults and hyperglycemia-mediated inflammation is central in DR. Toll-like receptors (TLRs) play a key role in innate immune responses and inflammation. However, scanty data is available on their role in DR. Hence, in this study, we examined TLR2 and TLR4 mRNA and protein expression and activity in hyperglycemic human retinal endothelial cells (HMVRECs). HMVRECs were treated with hyperglycemia (HG) or euglycemia and mRNA and protein levels of TL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(86 citation statements)
references
References 47 publications
(77 reference statements)
6
79
0
1
Order By: Relevance
“…In addition, antioxidant treatments reduce TLR-2 and TLR-4 expression and downstream inflammatory events. Collectively, these data suggest that hyperglycemia induces TLR-2 and TLR-4 activation and downstream inflammatory signaling, possibly through ROS [65].…”
Section: The Tlr-2 and -4 Inflammatory Signaling Pathwaysmentioning
confidence: 69%
See 1 more Smart Citation
“…In addition, antioxidant treatments reduce TLR-2 and TLR-4 expression and downstream inflammatory events. Collectively, these data suggest that hyperglycemia induces TLR-2 and TLR-4 activation and downstream inflammatory signaling, possibly through ROS [65].…”
Section: The Tlr-2 and -4 Inflammatory Signaling Pathwaysmentioning
confidence: 69%
“…In addition, TLR-2 and -4 signaling pathways appear to be the main triggers of these inflammatory responses. Recent in vitro studies have shown that high concentrations of glucose significantly increase TLR-2 and TLR-4 mRNA and protein expression in human microvascular ECs, as well as the activation of NF-κB p65, the expression of inflammatory markers such as interleukin (IL)-8, IL-1β, TNF-α, MCP-1, and vascular cell adhesion molecule (VCAM)-1 and intercellular adhesion molecule (ICAM)-1 [64,65]. All these events were reversed by TLR-4 or TLR-2 inhibition, or dual inhibition of these pathways by TLR4/2 inhibitory peptide.…”
Section: The Tlr-2 and -4 Inflammatory Signaling Pathwaysmentioning
confidence: 99%
“…TLR4 actively contributes to the infl ammatory response in development of microvascular complications, including diabetic retinopathy (Rajamani and Jialal 2014). Th e NFκB pathway is stimulated by hyperglycemia, reactive oxygen species, AGEs -all implicated in the pathogenesis of diabetes-associated vascular damage (Forbes and Cooper 2013).…”
Section: Discussionmentioning
confidence: 99%
“…High glucose conditions induce the overexpression of TLRs, such as TLR2 and TLR4 in endothelial cells in adipose tissue 72,133 , the retina 134 , coronary arteries 40 , and kidney tissues 135 . Endothelial cells exposed to fluctuating glucose concentrations induce an upregulation of TLR4 and TLR2 expression and this process has been associated with increased NFκB, IL8, MCP-1, ICAM-1, and VCAM-1 (Figure 3).…”
Section: [H2] Involvement Of Tlrsmentioning
confidence: 99%